The pseudo-hesiodic Shield of Heracles - Kudulytė-Kairienė, Audronė (Literatūra, 2015)
The article deals with the short epic poem known as The Shield of Heracles. This poem was ascribed to Hesiod in Antiquity, but nowadays the most scholars believe it was composed later than Hesiod’s other works, probably in the sixth century B.C. It tells about Heracles’ battle with Cycnus. The opening verses (1–56) of the poem are borrowed from the “Catalogue of Women”. The largest part of the work is the extended description of Heracles’ shield based on the shield of Achilles (Il. 18. 478–609). Various explanations of the poem’s date, authorship, composition, content and historical significance have been offered by modern scholars. Some literary versions of the legend of Cycnus are analysed in the present article. The Shield of Heracles was known to Stesichorus. It is supposed that in his poetry Stesichorus wanted to give more explanation of Apollo’s repugnance of Cycnus. For this reason the poet reexamined the myth and produced a new mythological version: Cycnus killed passers in order to build a temple for Apollo out of their heads. This version of the myth must has been used by Euripides (Eur. HF. 392 sqq.).